Dentists' restorative decision‐making and implications for an 'amalgamless' profession. Part 2: a qualitative study. (17th September 2014) - Alexander, G; Hopcraft, MS; Tyas, MJ; Wong, RHK
Abstract In some countries the use of amalgam has been restricted, and the dental profession may be forced into using alternatives to amalgam by a combination of public opinion and legislation, including the proposal that the material be 'phased‐down'. The limited research that exists as to restorative decision‐making is quantitative in nature and focuses on 'when' a restoration is placed. There is little qualitative research exploring 'why' a material is chosen. Purposive sampling of a representative group of dentists registered in Australia was carried out in two phases; initially six interviews followed by a focus group of six different participants who were audio‐recorded. Qualitative data were analysed using computer aided qualitative data analysis software. The findings suggest that dentists' restorative decision‐making is a complex interplay of factors. These may be categorized as 'clinical', 'knowledge', 'patient', 'practice type', 'biological' and 'environmental'. Use of amalgam is influenced by each of these to varying degrees. Quantitative analysis of the influences on restorative decision‐making is recommended. While the potential future 'phase‐down' of amalgam as a restorative material was of concern, there was a general sense of resignation or apathy to the matter. The implications for public health authorities, dental organizations and educators are noted.